The hedgehog pathway in breast cancer - Ali, Sheikh Asim (Chinese Journal of Cancer Research, 2012)
Breast cancer is one of the most common cancers around the world with approximately 1.6 million new cases and 425 thousand deaths from the disease in 2010 (1). While early detection methods and treatment have continuously evolved and improved over the years, there is still a strong need to further understand the pathways and mechanisms that lead to and drive this malignancy with the ultimate goal being more personalized, less toxic treatment with improved survival and higher cure rates.